Effect of direct and residual sewage-sludge application on physiological attributes of rice-wheat cropping system - JATAV, SURENDRA SINGH; SINGH, SATISH KUMAR; KUMAR, SUNIL; PARIHAR, MANOJ; PATRA, ABHIK; Rana, Kiran; Jatav, Hanuman Singh (The Indian Journal of Agricultural Sciences, 2022)
A two-year field experiment was conducted in 2017–19 to assess the growth and yield performance of rice–wheatcropping system (RWCS) as influenced by conjoint application of treated sewage sludge (TSS) and chemical fertilizerat Agricultural Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi, India. Thetreatments comprised control, 100% RDF [recommended dose of nitrogen (N), phosphorus (P) and potassium (K)],100% RDF +20 t/ha TSS, 100% RDF +30 t/ha TSS, 50% RDF +20 t/ha TSS, 60% RDF+20 t/ha TSS, 70% RDF +20 t/ha TSS, 50% RDF +30 t/ha TSS, 60% RDF +30 t/ha TSS, 70% RDF +30 t/ha TSS. The experiment was laidout in randomized block design with three replications. The results showed that higher growth, yield attributes and yield of rice and wheat were recorded under 100% RDF with 20 t/ha and 30 t/ha TSS as compared to 100% RDF alone. However, 70% RDF+ 30 t/ha TSS had given equivalent or higher yield as compared to 100% RDF in RWCS. Conjoint application of TSS along with chemical fertilizer i.e. 70% RDF with 20 t/ha and 30 t/ha TSS provided higher yield advantage without any harmful/negative impact on soil system and could be recommended as potential organic amendment for sustainable agricultural production system.